2005
DOI: 10.1099/vir.0.80489-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene organization and sequencing of the Choristoneura fumiferana defective nucleopolyhedrovirus genome

Abstract: Two distinct nucleopolyhedrovirus species of the eastern spruce budworm, Choristoneura fumiferana, exist in a symbiont-like relationship. C. fumiferana defective nucleopolyhedrovirus (CfDEFNPV) only infects C. fumiferana larvae per os in the presence of C. fumiferana nucleopolyhedrovirus Ireland strain (CfMNPV), but is infective when injected into the haemolymph. CfDEFNPV synergizes CfMNPV in per os infections and CfMNPV is always the predominant progeny. This study was undertaken to report the genomic makeup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 80 publications
1
28
1
2
Order By: Relevance
“…Even defective viruses, which often reduce the virulence of the virus population (e.g. Muñoz et al, 1998;Zwart et al, 2008), in some particular instances increase the virulence of the population when co-infecting with a helper virus (Lopez-Ferber et al, 2003;Lauzon et al, 2005). Here, however, we have identified a case were genetic heterogeneity is inversely correlated with disease outbreaks.…”
contrasting
confidence: 46%
“…Even defective viruses, which often reduce the virulence of the virus population (e.g. Muñoz et al, 1998;Zwart et al, 2008), in some particular instances increase the virulence of the population when co-infecting with a helper virus (Lopez-Ferber et al, 2003;Lauzon et al, 2005). Here, however, we have identified a case were genetic heterogeneity is inversely correlated with disease outbreaks.…”
contrasting
confidence: 46%
“…More recently, genomes of NPVs that infect hymenopteran species were also sequenced (Garcia- Maruniak et al, 2004;Lauzon et al, 2004;Duffy et al, 2006). Analysis of the available genomes has shown that 29 genes are conserved in all baculoviruses sequenced so far (Herniou et al, 2003;Garcia-Maruniak et al, 2004;Lauzon et al, 2005). This group of core genes represent a relatively small part of the over 800 different orthologous gene groups found in all baculovirus genomes up to the present date (Jehle et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In the field, baculoviruses occur as mixtures of conspecific genotypes (Miller, 1997;Hodgson et al, 2001). This genotypic diversity in a baculovirus population can be the result of genetic drift from a single parent strain, due to mutations, deletions and insertions during virus replication, or it can result from mixing and recombination of local and immigrant baculovirus strains (Williams, and Otvos, 2005;Lauzon et al, 2005;Jakubowska et al, 2005). Molecular engineering methods have been used to generate novel baculovirus genotypes with improved traits, notably speed of kill.…”
Section: Introductionmentioning
confidence: 96%